State and entrepreneurs facing situations of crisis: conditions and possibilities for diversification of production in Mendoza (1901-1939) - Rodríguez Vázquez, Florencia (2019)
The crises in Argentine winemaking during the first decades of the 20th century exposed its vulnerability, resulting from specialization in the cultivation of grape varieties for winemaking, susceptibility to pests and climatic contingencies, and a rigid supply that could not adapt to inelastic demand. These circumstances led to appraisals and a broad debate about the promotion of other production industries. The goal of this article is to describe the strengthening of diversification projects in Mendoza to com¬plement winegrowing (the central activity) and offset the adverse effects of chronic raw material surpluses. This led to the emergence of new industries during the 1920s and their consolidation, thanks to the impetus provided by the domestic market, in the 1930s. This process was ultimately driven by fruit production, based on state promotion and regulation and the arrival of extra-regional (wholesale merchants) and foreign agents.